Rethinking Language in Irigaray’s Mimesis Applied in David Mamet’s Oleanna - Shahrzad Mohammad Hossein; Narges Raoufzadeh; Fatemeh Sadat Basirizadeh (Budapest International Research and Critics University, 2020)
Throughout history, women have always sought their rights and place and this has long been the subject of much debate among writers and critics. So writers and critics, both men and women have reflected this issue in their works in different ways. From the very outset of her career, Luce Irigaray showed a keen interest in the exploration of the key role that language has in determining how women are evaluated in their society and the position they hold in it. In order to show resistance to masculine values imposed on them, women resort to strongholds such as mimesis in opposition. This paper aims to primarily, trace the backgrounds of this notion, secondly, to pursue the effect and use of it by women characters and to depict in what way it is employed as a means of resistance. Examples that will be provided shall be selected from the play “Oleanna”, a modern play written by David Mamet.